2016
DOI: 10.1002/app.43543
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polymerization shrinkage in dental restorative experimental composites based: BisGMA/TEGDMA, filled with MMT

Abstract: This work concerns to the investigation of the polymerization shrinkage and mechanical properties in dental restoratives experimental composites filled with nano clay Montmorilonite (MMT) Cloisite® 10A nanoparticles, in glycidyl methacrylate resin, using experimental composites filled with silanized Aerosil OX‐50 Silica as a control group. Six formulations with BisGMA/TEGDMA based polymeric matrix (three added with MMT and three added with silanized silica as filler) containing 50, 60, and 70 wt % were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
2
11
0
6
Order By: Relevance
“…PGL composites showed higher modulus with PLG up to 4 wt.% clay content, and no statistical differences were found for composites with higher clay content. Several authors [4,24,25] have also reported that flexural strength of nanocomposites decreased and modulus increased [8,10] as filler content increased.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…PGL composites showed higher modulus with PLG up to 4 wt.% clay content, and no statistical differences were found for composites with higher clay content. Several authors [4,24,25] have also reported that flexural strength of nanocomposites decreased and modulus increased [8,10] as filler content increased.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…Montmorillonite (MMT) is the most commonly used clay, both in its natural form and organically modified. Its use has been reported in Cloisite ® Na+ [6,7,9]; Cloisite ® 10A [10]; Cloisite ® 20A [6] and Cloisite ® 93A [7], although Cloisite ® 30B is the organoclay most employed [5][6][7]11].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that polymer-clay nanocomposites might present remarkable performance regarding their mechanical, physicochemical, thermal and antibacterial properties [18][19][20][21][22][23][24][25][26] . Recently, commercially available clay nanoparticles were utilized in composite resins exhibiting encouraging results concerning their polymerization shrinkage reduction and mechanical properties improvement [27][28][29] . Furthermore, commercially available 30) and experimental organomodified montmorillonites (OMMTs) 31) with variant alkylammonium cations were tested against representative pathogenic bacteria proving significant antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, storage modulus and thermal stability increment accompanied with slower polymerization rates and lower degrees of conversion were observed by incorporating up to 15 wt % OMMT with hexyltrimethylammonium bromide [42]. Intercalated nanocomposites containing 50, 60, and 70 wt % Cloisite 10A with lower polymerization shrinkage, high degree of conversion, and lower flexural strength compared to composites analogs filled with silanized silica were also reported [43]. The usage of 50, 60, and 65 wt % Cloisite 30B was found to induce lower polymerization shrinkage than silanized silica [44], while a similar degree of conversion and higher elastic modulus values in comparison to barium glass fillers were indicated at lower concentrations [45].…”
Section: Introductionmentioning
confidence: 99%